RENEWABLE ELECTRICAL ENERGY FROM WASTE (CASE STUDY OF WASTE AT JATIBARANG LANDFILL SEMARANG) - Hastarini Dwi Atmanti; I Made Bayu Dirgantara; Yuliani Setyaningsih (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
Renewable energy from waste can be an alternative as a power plant. This study aims to analyze the potential of waste in the Jatibarang landfill Semarang to be converted into electrical energy.The analytical method used is descriptive analysis. Around 850 tons of waste are dumped daily at the Jatibarang landfill. Due to the declining landfill capacity caused by this circumstance, the age of the landfill is decreasing. Waste must therefore be controlled by turning it into electrical energy. With a capacity of about 20 MW, this waste can be exploited as a power source.An environment with a sustainability quality will result from the conversion of waste into electrical energy.